KAJIAN EKOLINGUISTIK SIKAP MAHASISWA TERHADAP UNGKAPAN PELESTARIAN LINGKUNGAN DI UNIVERSITAS NEGERI SEMARANG - Yuniawan, Tommi; Masrukhi, Masrukhi; Alamsyah, Alamsyah (Indonesian Journal of Conservation, 2014)
Semarang State University became University of Conservation on 12 March 2012. This influences the policy-making as well as efforts in socializing and empowering the entire campus community in creating and cementing this conservation vision. There are some mottoes that are used to uphold the principle of protection, preservation, utilization and sustainable development of natural resources and cultural arts, in order to preserve the environment of this conservation campus, for example, " Salam Konservasi " which means go conservation, "Thousand tree-planting movement,â€ " Pasar Krempyeng Nyeniâ€ which promote the Arts of Krempyeng Market, "On Campus: Letâ€™s Walk or Cycle!", "Planting Trees, Planting Hope", "Motorcycle Free ". Student participation in developing the University of Conservation is one of the keys to successfully implement UNNES vision. In terms of quantity, the students occupy the largest portion compared to faculties and staffs. Reciprocal changes occurred between the environment and the languages were learned through ecolinguistics study. Ecolinguistic study examines the ecosystem as a part of the human life system (ecology) and the language used by humans to communicate in their environment (linguistics). This means the studentsâ€™ attitudes towards the conservation mottoes in campus will influence personal behaviours and communities of college students in preserving the environments.Â Keywords: ecolinguistics, conservation, student attitudes, mottoes of environmental conservation.Â Universitas Negeri Semarang menjadi Universitas Konservasi pada 12 Maret 2012. Hal ini berimplikasi adanya kebijakan dan upaya yang dilakukan untuk mensosialisasikan, memahamkan, serta menggerakkan seluruh warga kampus dalam mewujudkan dan mengokohkan visi konservasi ini. Artinya, ada ungkapan-ungkapan yang digunakan untuk selalu menjunjung tinggi prinsip perlindungan, pengawetan, pemanfaatan, dan pengembangan secara lestari terhadap sumber daya alam dan seni budaya, dalam pelestarian lingkungan di kampus konservasi ini. Misalnya, â€œSalam Konservasiâ€, â€œGerakan Tanam Seribu Batang pohonâ€, â€œPasar Krempyeng Nyeniâ€, â€œDi Kampus: Jalan Kaki atau Bersepeda, Yuk!â€,Â  â€œMenanam Pohon, Menanam Harapanâ€, â€œBebas Sepeda Motorâ€. Partisipasi mahasiswa dalam pengembangan Universitas Konservasi merupakan salah satu kunci keberhasilan penerapan visi Unnes. Hal ini disebabkan ditinjau dari segi kuantitas, mahasiswa menempati porsi paling banyak dibandingkan dengan dosen dan tenaga kependidikan. Perubahan timbal balik antara lingkungan dan bahasa dipelajari melalui kajian ekolinguistik. Kajian ekolinguistik mengkaji ekosistem yang merupakan bagian dari sistem kehidupan manusia (ekologi) dengan bahasa yang dipakai manusia dalam berkomunikasi dalam lingkungannya (linguistik). Artinya, sikap mahasiswa terhadap ungkapan-ungkapan pelestarian lingkungan di kampus konservasi akan mempengaruhi perilaku pribadi maupun komunitas mahasiswa dalam berkonservasi.Kata kunci: ekolinguistik, konservasi, sikap mahasiswa, ungkapan pelestarian lingkungan.Â